Everyday Europe social transnationalism in an unsettled continent - Recchi, Ettore ca. 20./21. Jh (Policy Press, 2019)
This book offers an empirically-based view on Europeans' interconnections in everyday life. It looks at the ways in which EU residents have been getting closer across national frontiers. The book considers how people reconcile their increasing cross-border interconnections and a politically separating Europe of nation states and national interests
Title from publisher's bibliographic system (viewed on 07 Apr 2022)
Keywords: Transnationalism / Social aspects / European Union countries; Globalization / European Union countries; Nationalism / European Union countries; Einstellung; Netzwerk; Transnationale Politik; Nationalstaat; European Union countries / Politics and government / 21st century; Europa; Aufsatzsammlung